CLEANING EFFICACY OF DIFFERENT FINAL IRRIGATION ACTIVATION TECHNIQUES - MUSTAFA, BIZHYAN MAHDI; SELIVANY, BAHAR JAAFAR (Journal of Duhok University, 2023)
Purpose: The cleaning effectiveness of ultrasonic, diode laser, XP endo finisher, and finsher gentlefile brush was assessed and compared.Methods: 40 single-rooted mandibular premolars extracted and decoronated to a coronal length of 12 mm to the apex, biomechanically instrumented with protaper Next up to size X3. The roots were then randomly divided into four groups (n=10) and received a final irrigation and activation. GI: Ultrasonic system activated the final irrigant, GII: 980-nm diode laser, GIII: Xp-endo finisher, GIV: Finisher gentle file-brush. Under a scanning electron microscope, the teeth were longitudinally sectioned into two halves and scored. To compare groups, the Kruskal-Wallis Test was used, and P 0.05 was regarded as statistically significant.Results: Finisher gentle file brush was most efficient in removing the smear layer, with a statistically significant difference with Diode laser (p<0.0037) and XP EndoFinisher (p<0.0198). There was no statistically significant difference in the Debris removal between all groups.Conclusions: No irrigation activation technique was able to eliminate debris and smear layer completely from root canals. The Finisher gentle file brush was most efficient in removing smear layer. Diode laser showed the least smear layer removal